The End of Anthropology? - Comaroff, John (Sean Kingston Publishing, 2011)
Decolonisation, modernisation, globalisation, the crisis of representation, and the 'cultural turn' in neighbouring disciplines have unsettled anthropology to such an extent that the field's foundations, the subjects of its study as well as its methods and concepts, appear to be eroded. It is now time to take stock and either abandon anthropology as a fundamentally untenable or superfluous project, or to set it on more solid foundations. In this volume some of the world's leading anthropologists - including Vincent Crapanzano, Maurice Godelier, Ulf Hannerz and Adam Kuper - do just that. Reflec.